An overview of the approaches and methods for analysing a text from a discursive viewpoint - Hernández-Guerra, Concepción (Onomázein, 2014)
Discourse analysis is a modern discipline that has inherited lots of attributes from text analysis. So broad is the range of texts and so different the perspectives under which these texts can be analyzed that we can easily understand the different fields that discourse analysis as a whole can cover. The aim of this paper is twofold: firstly, to clarify the different terms included in the discourse in order to separate the features of this discipline from others, and, secondly, to offer a general vision of all the methods that can be carried out under this umbrella to take the most of the data to be analyzed